2015
DOI: 10.1021/la504752u
|View full text |Cite
|
Sign up to set email alerts
|

Single-Vesicle Detection and Analysis of Peptide-Induced Membrane Permeabilization

Abstract: The capability of membrane-active peptides to disrupt phospholipid membranes is often studied by investigating peptide-induced leakage of quenched fluorescent molecules from large unilamellar lipid vesicles. In this article, we explore two fluorescence microscopy-based single-vesicle detection methods as alternatives to the quenching-based assays for studying peptide-induced leakage from large unilamellar lipid vesicles. Specifically, we use fluorescence correlation spectroscopy (FCS) to study the leakage of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Altogether, these site-specific peptide probes enabled us to view water penetration into the hydrophobic region of the bilayer, which may be otherwise thermodynamically unfavorable in peptide-free bilayers. Previous literature has observed negligible water presence beyond the ester carbonyl in pure lipid membranes (75)(76)(77) and has also suggested that embedded amino acids and peptides may facilitate water diffusion across lipid bilayers and into the alkyl bulk (6,(78)(79)(80)(81)(82). Our results are consistent with this literature; however, additional methods beyond the scope of this study are required to rule out potential peptide multimers in the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Altogether, these site-specific peptide probes enabled us to view water penetration into the hydrophobic region of the bilayer, which may be otherwise thermodynamically unfavorable in peptide-free bilayers. Previous literature has observed negligible water presence beyond the ester carbonyl in pure lipid membranes (75)(76)(77) and has also suggested that embedded amino acids and peptides may facilitate water diffusion across lipid bilayers and into the alkyl bulk (6,(78)(79)(80)(81)(82). Our results are consistent with this literature; however, additional methods beyond the scope of this study are required to rule out potential peptide multimers in the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…20 This dye, as well as other members of the carbocyanine dye family, have been widely used to label cell membranes, [21][22][23] viruses, 9,10,24 exosomes 12,25,26 and synthetic liposomes. [27][28][29][30][31] From a structural point of view, lipophilic carbocyanine dyes, are symmetric molecules consisting of two aromatic cyanine moieties joined by three methine groups, which together constitute the fluorophore part of the molecule. Furthermore, to introduce lipophilicity, alkyl chains are conjugated to each cyanine moiety as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy of pretreating dye-loaded vesicles with a pore-forming antimicrobial peptide before immobilizing the vesicles onto a surface for confocal imaging has also been utilized to characterize three peptides, mastoparan X, melittin, and magainin 2, while focusing on the percentage of fully dyeemptied vesicles and the average percentage of dye release per vesicle after the membrane−peptide interaction was completed. 146 To date, the reported tethering strategies have focused on synthetic lipid vesicles, while it would be advantageous to further develop labeling and tethering strategies to attach authentic, enveloped virus particles to surfaces. From a biosensing perspective, the transition from virus-mimicking model membrane systems to actual virus particles would represent a major advance to directly understand how membrane-disruptive compounds affect enveloped virus particles.…”
Section: Biosensing Tools For Antiviral Drug Developmentmentioning
confidence: 99%
“…Using this approach, it was discovered that antiviral peptides can disrupt not only individually tethered vesicles but also clusters of tethered vesicles. An alternative strategy of pretreating dye-loaded vesicles with a pore-forming antimicrobial peptide before immobilizing the vesicles onto a surface for confocal imaging has also been utilized to characterize three peptides, mastoparan X, melittin, and magainin 2, while focusing on the percentage of fully dye-emptied vesicles and the average percentage of dye release per vesicle after the membrane–peptide interaction was completed …”
Section: Biosensing Tools For Antiviral Drug Developmentmentioning
confidence: 99%